REVITALISASI TATA LAMBANG KOMUNIKASI TRADISIONAL WAYANG INDONESIA SEBAGAI MILIK DONIA - Kertopati, Ton (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2010)
We now come to the consideration of convergence, an issue that seems to be particularly vecing to social scientists especially cultural. Much of the difficulty of dealing with this problem stem from the failure to distinguish with sufficient precision the different elements of a very complex situation. A minimum list of such elements should include the following: a.Structures of patterns of social relationship. b.System of popular attitudes, value and behavior. c. System ofpolitical and economic control.